Kemampuan Menganalisis Makna Tersirat Struktur Teks Hikayat “Si Miskin” Siswa Kelas X SMA Muhammadiyah 1 UNISMUH Makassar (Jurnal Motivasi Pendidikan dan Bahasa, 2023)
The aim of this study is to find out the ability to analyze the implied meaning of the text structure of the saga "The Miskin" Muhammadiyah Makassar SMA students. The type of research used in this research is descriptive quantitative research. This research was conducted at SMA Muhammadiyah 1 Unismuh Makassar. This research took the number of subjects as many as 27 students from class X IPA. Selected by using purposive sampling. The results of the analysis are based on the Ability to Analyze Implied Meanings in the Text Structure of the Hikayat "The Miskin" Class X SMA Muhammadiyah 1 Unismuh Makassar. The research results showed that only 11 students achieved the KKM standard with a percentage of 40.74% and students who scored below the KKM still had 16 students with a percentage of 50.26% which was still very low. it is known that the average score in the abstraction analysis is 16.81, the orientation analysis is 15.51, the complication analysis is 14.92, the evaluation analysis is 9.88, the resolution analysis is 9.74, the coda analysis is 8, and the overall average in the assessment and final score 74,66. So the ability to analyze the implied meaning of the text structure is still very low.